LARGE CHIROTHERIIDAE TRACKS IN THE EARLY TRIASSIC OF WIÓRY, HOLY CROSS MOUNTAINS, POLAND - Niedźwiedzki G.; Ptaszyński T. (My University, 2007)
Very large chirotheriid tracks have been discovered in the Early Triassic Wióry Formation (=Labyrinthodontidae and Hieroglyphic Beds), middle part of the Middle Buntsandstein, exposed at Wióry in the northeastern part of the Holy Cross Mountains (central Poland). Hitherto, six small and medium-sized chirotheriid tracks from-the Wióry locality have been-described. In the present paper two ichnotaxa are proposed: Synaptichnium senkowiczowae ichnosp. nov. and Brachychirotherium kalkowensis ichnosp. nov. Their presumed trackmakers, large Early Triassic (Olenekian) Archosauriformes (Proterosuchidae, Erythrosuchidae), about 5-7 m long, are unknown from the osteological record of this age worldwide. The newly described ichnotaxa represent the oldest known record of large chirotheriid tracks in the Middle Buntsandstein of Poland. The presence of large chirotheriid tracks in the upper part of the Early Thassic deposits is very important for the understanding of the evolution and radiation of early Archosauromorpha, as well as for reconstructing Early Triassic terrestrial palaeoecosystems.
Keywords: ARCHOSAUROMORPHA; BUNTSANSTEIN; CHIROTHERIIDAE; LOWER TRIASSIC; POLAND; VERTEBRATE TRACKS; Olenekian; Mesozoic::Triassic::Lower::Olenekian; Мезозой::Триасовая::Нижний::Оленёкский